The Validity of Long-Distance Marriages Conducted via Virtual Media in the Perspectives of Keruak’s Ulama and Muslim Intellectuals - Uswatun Ni’ami (LP2M STIT Palapa Nusantara, 2025)
This study is motivated by the limited empirical research on the religious and socio-legal perspectives of local Islamic authorities regarding virtual marriage, despite its growing relevance in the context of digital communication and transnational mobility. The study aims to analyze how ulama and Muslim intellectuals in Keruak perceive the validity of long-distance marriages conducted via virtual media, to identify the legal and theological foundations underlying their views, and to examine the social implications of these perspectives. The research adopts a qualitative case study design, with 28 participants selected through purposive sampling, consisting of ulama, Muslim intellectuals, and community-administrative informants. Data were collected through semi-structured interviews, observations, and document analysis, and analyzed using thematic analysis. The findings reveal that virtual marriage discourse remains at a normative–theoretical level, with no empirical implementation in Keruak. Although participants acknowledge jurisprudential flexibility when essential pillars of marriage are fulfilled, they emphasize legal certainty, identity verification, and evidentiary reliability. Religious reasoning integrates classical fiqh munākahāt with maqāṣid al-syarī‘ah, leading to a conditional, risk-sensitive stance prioritizing the protection of lineage, dignity, and social order. The study concludes that the absence of virtual marriage practice reflects regulatory ambiguity, institutional caution, and strong communal ritual norms rather than categorical theological rejection. Theoretically, the study contributes to socio-religious legal scholarship on digital mediation in Islamic family law. Practically, it highlights the need for regulatory clarification and technological safeguards. Future research should explore comparative contexts and institutional pilot implementations.